2022
DOI: 10.3390/jcm11195831
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus Robotic Hepatectomy: A Systematic Review and Meta-Analysis

Abstract: This study aimed to assess the surgical outcomes of robotic compared to laparoscopic hepatectomy, with a special focus on the meta-analysis method. Original studies were collected from three Chinese databases, PubMed, EMBASE, and Cochrane Library databases. Our systematic review was conducted on 682 patients with robotic liver resection, and 1101 patients were operated by laparoscopic platform. Robotic surgery has a long surgical duration (MD = 43.99, 95% CI: 23.45–64.53, p = 0.0001), while there is no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…This rate is higher than other studies, which have reported conversion rates of 0-12% for laparoscopic and 0-20% for robotic hepatic resections. [28][29][30][31][32][33][34] It should be noted that several of the studies listed did not specify the indication for resection, only laparoscopic vs robotic, when comparing conversion rates. Conversion to open resection typically occurs due to uncontrolled hemorrhage, difficulty achieving adequate oncologic resection, or general lack of progress in performing the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is higher than other studies, which have reported conversion rates of 0-12% for laparoscopic and 0-20% for robotic hepatic resections. [28][29][30][31][32][33][34] It should be noted that several of the studies listed did not specify the indication for resection, only laparoscopic vs robotic, when comparing conversion rates. Conversion to open resection typically occurs due to uncontrolled hemorrhage, difficulty achieving adequate oncologic resection, or general lack of progress in performing the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions from retrospective studies and meta‐analyses comparing RH to LH are more variable. For perioperative outcomes, RH requires a longer operative time but is consistently associated with a lower conversion rate than LH ( p < 0.001) 109–112 . In most other surgical procedures, a robotic approach is associated with decreased operative blood loss compared to a laparoscopic approach.…”
Section: Hepato‐pancreato‐biliary Surgerymentioning
confidence: 99%
“…For perioperative outcomes, RH requires a longer operative time but is consistently associated with a lower conversion rate than LH (p < 0.001). [109][110][111][112] In most other surgical procedures, a robotic approach is associated with decreased operative blood loss compared to a laparoscopic approach. However, because there is currently no robotic Cavitron ® Ultrasonic Surgical Aspirator (CUSA) (Integra LifeSciences, Tullamore, Ireland), RH is mainly performed using the crush clamp technique, thus leading to higher operative blood loss.…”
Section: Robotic Versus Laparoscopic Hepatectomymentioning
confidence: 99%
See 2 more Smart Citations